Structured object-oriented formal language and method : 5th International Workshop, SOFL+MSVL 2015, Paris, France, November 6, 2015, Revised selected papers /: 5th International Workshop, SOFL+MSVL 2015, Paris, France, November 6, 2015, Revised selected papers. (2016) - Unknown
No abstract available